Impact of the type of mask on the effectiveness of and adherence to continuous positive airway pressure treatment for obstructive sleep apnea - Rafaela Garcia Santos de Andrade; Vivien Schmeling Piccin; Juliana Araújo Nascimento; Fernanda Madeiro Leite Viana; Pedro Rodrigues Genta; Geraldo Lorenzi-Filho (Jornal Brasileiro de Pneumologia, 2014)
Continuous positive airway pressure (CPAP) is the gold standard for the treatment of obstructive sleep apnea (OSA). Although CPAP was originally applied with a nasal mask, various interfaces are currently available. This study reviews theoretical concepts and questions the premise that all types of interfaces produce similar results. We revised the evidence in the literature about the impact that the type of CPAP interface has on the effectiveness of and adherence to OSA treatment. We searched the PubMed database using the search terms "CPAP", "mask", and "obstructive sleep apnea". Although we identified 91 studies, only 12 described the impact of the type of CPAP interface on treatment effectiveness (n = 6) or adherence (n = 6). Despite conflicting results, we found no consistent evidence that nasal pillows and oral masks alter OSA treatment effectiveness or adherence. In contrast, most studies showed that oronasal masks are less effective and are more often associated with lower adherence and higher CPAP abandonment than are nasal masks. We concluded that oronasal masks can compromise CPAP OSA treatment adherence and effectiveness. Further studies are needed in order to understand the exact mechanisms involved in this effect.